Il pleistocene medio-superiore nella carota di ghiaccio di Talos Dome (antartide orientale): riscostruzione ad alta risoluzione del record delle polveri fini atmosferiche e loro significato paleoclimatico - MAZZOLA, CLAUDIA MARIA GABRIELLA (Università degli Studi di Milano-Bicocca, 2009)
The study of the past global climatic variations plays a very important role in the comprehension of present climate change and in the assessment of its future development. In particular, it is important to understand the natural variability of the climatic system and in which way human activity is responsible for these variations. Paleoclimatic studies are based on information preserved in Natural Archives, sites around the world where it is possible to obtain indirect data, the so called proxy data, about climate-dependant parameters. Polar Ice Caps are one of the better natural archives both in terms of preservation and completeness. During the last two decades many drillings were performed in both Antarctic and Greenlandic ice caps, and in particular three ice cores from East Antarctic plateau have allowed to investigate a long period of past climate. These are Vostok ice core (Petit et al, 1999), Dome Fuji ice core (Goto-Azuma, 2006), and EPICA (European project for Ice Coring in Antarctica) Dome C ice core (EPICA community members, 2004). The last one covers 800,000 years BP (Before Present), and contains the oldest ice ever drilled. It is possible to collect many information from ice cores, and this work is focused on mineral dust concentration variability in the East Antarctic ice sheet, with the aim to create a very high resolution dust record. Atmospheric dust that has reached and deposited on Antarctic ice sheet from remote areas, are considered one of the best-preserved and detailed proxy data. Dust concentration, size distribution, isotopic signature and mineralogical studies give us information about climate variability and potential source areas (PSA), moreover it is possible to reconstruct paleoatmospheric circulation and back trajectories through models. In this way it is possible to contribute in increasing knowledge about coupled ocean-atmospheric system dynamics and about the important and not completely understood climate forcing role of the dust. In this work dust concentration was ...